An experimental study on intraoperative recovery of recurrent laryngeal nerve function. Issue 5 (4th September 2020) - Setså, Erling J.; Svendsen, Øyvind S.; Husby, Paul J.; Heimdal, John‐Helge; Stangeland, Lodve; Dahle, Geir O.; Brauckhoff, Katrin
Abstract: Objective: If bilateral thyroid surgery is planned and staged thyroidectomy considered in case of loss of neuromonitoring signal (LOS), a waiting time of 20 minutes is suggested for evaluation of early nerve recovery. This recommendation is based on clinical observations and has not been thoroughly validated experimentally. Methods: Sixteen pigs were randomly studied, and electromyogram (EMG) was continuously recorded during traction injury until an amplitude decrease of 70% from baseline (BL) (16 nerves) or LOS (16 nerves), and further during 40‐minute recovery time. At the end of the experiments, vocal cord twitch was evaluated by video‐laryngoscopy. Results: In the 70% group, 8 of 16 nerves recovered to or above an amplitude of 50% of baseline after 20 minutes and finally one more after 40 minutes. In the LOS group, only one nerve showed recovery after 20 minutes and one more after 40 minutes. Video‐laryngoscopy revealed good or strong vocal cord twitches, in 10 of 14 nerves in the 70% group and in only 2 of 14 nerves in the LOS group. Conclusions: The overall intraoperative recovery was low after LOS. Even after 70% amplitude depression, only half of the nerves showed recovery to amplitudes ≥50% of BL. Nerve recovery is dynamic, and a waiting time of 20 minutes seems appropriate for the identification of early nerve recovery before decisions are taken to continue or terminate surgery. The final EMG amplitude was not always well correlated with estimated vocal cord twitch, evaluated by video‐laryngoscopy. This observation needs further investigation. Abstract :